1989
DOI: 10.1007/bf00439461
|View full text |Cite
|
Sign up to set email alerts
|

Effects of route of administration of ethanol on high-speed reaction time in young and old rats

Abstract: The blood ethanol concentrations (BECs) and reactive capacity of young (8 months) and old (24 months) male Fischer 344 rats were compared at 5, 10, 20, 45, 65, and 90 min following the administration of ethanol (EtOH). The time-dependent effects of intragastric intubation (IG; 3 g/kg) and intraperitoneal injection (IP; 1.5 g/kg) of EtOH (20% w/v) were determined. Subsequent to IG delivery, BECs rose most rapidly within the first 20 min, but did not reach peak levels until 90 min for both young (240 mg/dl) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Such sub-optimal representations may be a primary determinant of age-related increases in performance inconsistency and cognitive deficits. Experimental data from both human (age-related declines in dopamine are associated with poorer attention, memory, and motor performance: e.g., Arnsten, 1993;Bäckman et al, 2000) and animal research (catecholaminergic modulation determines performance speed and variability: e.g., MacRae, Spirduso, & Wilcox, 1988;Spirduso, Mayfield, Grant, & Schallert, 1989) support this hypothesis. Conceivably then, variability at the neurological level may underlie agerelated increases in inconsistency and declines in mean cognitive performance at the behavioral level (e.g., Lindenberger, Li, & Brehmer, 2002;Myerson, Hale, Wagstaff, Poon, & Smith, 1990;Welford, 1980).…”
mentioning
confidence: 64%
“…Such sub-optimal representations may be a primary determinant of age-related increases in performance inconsistency and cognitive deficits. Experimental data from both human (age-related declines in dopamine are associated with poorer attention, memory, and motor performance: e.g., Arnsten, 1993;Bäckman et al, 2000) and animal research (catecholaminergic modulation determines performance speed and variability: e.g., MacRae, Spirduso, & Wilcox, 1988;Spirduso, Mayfield, Grant, & Schallert, 1989) support this hypothesis. Conceivably then, variability at the neurological level may underlie agerelated increases in inconsistency and declines in mean cognitive performance at the behavioral level (e.g., Lindenberger, Li, & Brehmer, 2002;Myerson, Hale, Wagstaff, Poon, & Smith, 1990;Welford, 1980).…”
mentioning
confidence: 64%
“…Furthermore, many experimental studies have demonstrated that age-related deterioration in the dopaminergic systems are closely related to age-related memory, attention [72][73][74] and motor [73,75,76] deficits. Of particular relevance here are the findings showing that old rats and monkeys with less efficient dopaminergic modulation not only exhibited increased motor reaction and movement time, the variability in their RTs also increased [77][78][79]. Therefore, the less efficient dopaminergic modulation could be one possible source of increased intraindividual fluctuations in old people's sensorimotor performance.…”
Section: An Integrative Approach To Understanding the Increasing Sensmentioning
confidence: 87%
“…Interestingly, the effects of ethanol on reaction time did not interact with time block, suggesting that ethanol's effects on reaction time cut across the entire task, and consequently may not have significantly contributed to the vigilance decrement. The interpretation of the absence of a time-dependent change in reaction time is complicated by the potential development of acute tolerance and changes in blood ethanol concentration (BEC), both of which may influence reaction time (Spirduso 1989). Additional experiments in which ethanol is administered at different time points relative to behavioral testing are required to determined the relationship between changes in BEC, behavioral tolerance, and reaction time.…”
Section: Discussionmentioning
confidence: 99%
“…Performance in these tasks is impaired by a number of pharmacological treatments, including drugs active at benzodiazepine, dopamine and acetylcholine receptors (McGaughy and Sarter 1995;Muir et al 1995). Whereas ethanol has been tested in rats on a number of reaction time tasks (Koob et al 1988;Spirduso et al 1989;Mayfield et al 1992), the effects of ethanol on performance of an explicit sustained attention task in rats has not been tested to date.…”
Section: Introductionmentioning
confidence: 97%